Effects of external insulation component on thermal performance of a Trombe wall with phase change materials. (1st July 2020) - Liu, Yan; Hou, Liqiang; Yang, Yidong; Feng, Yinping; Yang, Liu; Gao, Qinglong
Highlights: PCM and insulation component are used to improve thermal performance of Trombe wall. Effects of design parameters of insulation component are studied using the validated model. Design approach of heat preservation at night of a TW-PCM is proposed. Thermal comfort is analyzed based on operative temperature and radiant temperature asymmetry. Abstract: A classical Trombe wall cannot satisfy the thermal comfort for the whole day due to the limited heat storage capacity and large heat loss at night. In present work, phase change materials and an external insulation component are used to improve thermal performance of a Trombe wall. The design approach of heat preservation at night is first obtained. An unsteady heat transfer model of a Trombe wall with phase change materials under heat preservation condition in the nighttime is established by MATLAB. The reliability of the mathematical model is validated by an experiment in Yuzhong (Gansu, China). With this model, the effects of the design parameters of the external insulation component on the thermal performance are analyzed. Finally, the indoor thermal comfort of a passive solar room is analyzed based on the experimental data. The results indicate that, it has a significant impact of the thermal conduction resistance of the insulation component and the thermal resistance of the closed air cavity. For closed air cavity, the internal surface emissivity of the insulation component plays an important role. The optimized additional thermal resistance for the external insulation component is 2 m 2 ⋅°C⋅W −1, and the corresponding maximum thermal resistance of the closed air cavity is determined as about 0.5 m 2 ⋅°C⋅W −1 . Compared with no heat preservation at night, the operative temperature improves significantly, and the radiant temperature asymmetries of two massive walls are similar. The investigation can provide a design approach of heat preservation at night for a Trombe wall.